2017
DOI: 10.15448/1980-6523.2017.2.26479
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of propolis in subcutaneous tissue of rats: a possible biomaterial for cavity cleansing

Abstract: OBJECTIVE: The aim of this study was to histopathologically analyze, in subcutaneous connective tissue in rats, a propolis solution for cavity cleansing and its toxicity through hemolytic and Artemia franciscana tests. METHODS: Fifteen male rats were selected and randomly distributed in three experimental periods (07, 30 and 45 days), in which each animal received the four treatment groups in rounds: Group IPropolis I; Group II -Propolis II; Group III -Calcium Hydroxide Water and Group IV -2% Chlorexidine; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In the cytotoxicity test using Artemia franciscana, the propolis extract showed high toxicity in the tested concentrations, and in the hemolytic activity test, the Propolis I extract showed more activity than Propolis II. Therefore, the present study suggested the use of propolis as a cavity cleansing solution for shallow and medium cavities similarly to the use of 2% chlorhexidine ® [15].…”
Section: Apis Mellifera-propolismentioning
confidence: 79%
See 2 more Smart Citations
“…In the cytotoxicity test using Artemia franciscana, the propolis extract showed high toxicity in the tested concentrations, and in the hemolytic activity test, the Propolis I extract showed more activity than Propolis II. Therefore, the present study suggested the use of propolis as a cavity cleansing solution for shallow and medium cavities similarly to the use of 2% chlorhexidine ® [15].…”
Section: Apis Mellifera-propolismentioning
confidence: 79%
“…Almeida et al [15] reported that propolis is a complex mixture of resinous, gummy, and balmy substances collected by A. mellifera bees. It has a bactericide, antimicrobial, antioxidant, anti-inflammatory, immunomodulatory, hypotensive, anesthetic, anti-cancerous, anti-HIV, and anti-carious biologic function.…”
Section: Apis Mellifera-propolismentioning
confidence: 99%
See 1 more Smart Citation
“…This research revealed that propolis nanoparticle sealer could be applied as a substitute for the current sealer, which had a toxic effect. b) Research by Almeida et al [61] analysed the toxicity of propolis ethanol extract using Artemia franciscana (A. franciscana) as a model. In the plates, ten Artemia franciscana nauplii were given 20 mL of ethanol extract of propolis at a concentration of 8% and incubated for 24 hours at room temperature in the dark.…”
Section: In Vivo Propolis Biocompatibilitymentioning
confidence: 99%